2011
DOI: 10.1021/bc200258x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pretargeted and Conventional CC49 Radioimmunotherapy Using 149Pm, 166Ho, and 177Lu

Abstract: The therapeutic efficacies of radiolabeled biotin, pretargeted by monoclonal antibody (mAb)-streptavidin fusion protein CC49 scFvSA, were compared to those of radiolabeled mAb CC49, using the three radiolanthanides in an animal model of human colon cancer. The purpose of the present study was to compare antibody pretargeting to conventional radioimmunotherapy using (149)Pm, (166)Ho, or (177)Lu. Nude mice bearing LS174T colon tumors were injected sequentially with CC49 scFvSA, the blood clearing agent biotin-Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…In the second strategy, antibodies covalently modified with oligomeric nucleic acids are used as the targeting vectors while radiolabeled, complementary oligonucleotide sequences are used as the radioligands (8). Both systems are creative solutions and have proven successful in vivo (9,10). Each, however, possesses significant limitations that threaten their clinical applicability.…”
mentioning
confidence: 99%
“…In the second strategy, antibodies covalently modified with oligomeric nucleic acids are used as the targeting vectors while radiolabeled, complementary oligonucleotide sequences are used as the radioligands (8). Both systems are creative solutions and have proven successful in vivo (9,10). Each, however, possesses significant limitations that threaten their clinical applicability.…”
mentioning
confidence: 99%
“…Clearly a therapeutic reagent which dissipates most of its energy before it reaches its biological target will do more harm than good. For example, Lewis and co-workers 136 reported a comparison of 149 Pm, 166 Ho and 177 Lu for use in CC49 radioimmunotherapy.…”
Section: Future Prospects and Untapped Potentialmentioning
confidence: 99%
“…[83][84][85][86][87][88][89][90][91][92][93][94][95] These computational models were also integrated in comparative Monte Carlo-based simulations studies investigating patterns of uptake and biodistribution data of radiopharmaceuticals for the purpose of dose estimation in molecular radiotherapy and diagnostic nuclear medical imaging procedures. [96][97][98][99][100][101][102][103][104][105][106][107] For external exposure to ionizing radiation, few studies reported on the calculation of organ dose conversion coefficients for small animals under ideal irradiation conditions (left lateral, right lateral, dorsal-ventral, ventral-dorsal, and isotropic irradiation directions), 26,40 therapeutic irradiation conditions, 23 and diagnostic imaging x-ray irradiations. 60 A number of studies have evaluated factors influencing small animal internal radiation dosimetry.…”
Section: A Ionizing Radiation Dosimetrymentioning
confidence: 99%